2003
DOI: 10.1021/ja027658s
|View full text |Cite
|
Sign up to set email alerts
|

A New Horner−Wadsworth−Emmons Type Coupling Reaction between Nonstabilized β-Hydroxy Phosphonates and Aldehydes or Ketones

Abstract: Treatment of nonstabilized beta-hydroxy phosphonic acid mono methyl esters with diisopropyl carbodiimide at ambient temperature leads to clean stereospecific elimination. The phosphonic acid mono alkyl esters are accessible by the selective partial saponification of dimethyl or diethyl alkyl phosphonates with NaOH or MgBr(2). Isolated yields over both hydrolysis and elimination steps average 55-75%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…37 Treatment of 34 with n-butyllithium and the aldehyde 32 gave the adduct 35 , which partly eliminated to the olefin 4 . Treatment of the residual 35 with MgBr 2 and heating was expected to provide the corresponding phosphate monoester 38 but gave instead the target olefin 4 . The combined 4 containing fractions were purified chromatographically (2.7%).…”
Section: Resultsmentioning
confidence: 99%
“…37 Treatment of 34 with n-butyllithium and the aldehyde 32 gave the adduct 35 , which partly eliminated to the olefin 4 . Treatment of the residual 35 with MgBr 2 and heating was expected to provide the corresponding phosphate monoester 38 but gave instead the target olefin 4 . The combined 4 containing fractions were purified chromatographically (2.7%).…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, olefination using nonstabilized HWE reagents has been viewed as a difficult transformation. However, a report by Reichwein and Pagenkopf showed that the resulting hydroxyphosphonate undergoes elimination via a saponification–dehydration sequence . To our delight, this was indeed the case when we subjected our substrate to the reported conditions using unlabeled dimethyl methylphosphonate.…”
Section: Resultsmentioning
confidence: 73%
“…However, a report by Reichwein and Pagenkopf showed that the resulting hydroxyphosphonate undergoes elimination via a saponification-dehydration sequence. 3 To our delight, this was indeed the case when we subjected our substrate to the reported conditions using unlabeled dimethyl methylphosphonate. Encouraged by this initial result, we prepared the [ 14 C]-HWE reagent via the Michaelis-Arbuzov reaction.…”
Section: Resultsmentioning
confidence: 82%
“…Direct phosphonate olefination is limited in scope since β-hydroxy phosphonates lacking electron withdrawing substituents on the α-carbon are not prone to eliminate without activation. 22 However, Corey 23 found that β-hydroxy thionophosphonates readily undergo elimination to form alkenes. Treating phosphonate 17 with Lawesson’s reagent 24 affords thionophosphonate 18 .…”
mentioning
confidence: 99%